Utilization of Bengkok Land by Means of a Rental System to Steam Power Plants and Communities in Tubanan Village, Jepara Regency: Pemanfaatan Tanah Bengkok dengan Cara Sistem Sewa Kepada Pembangkit Listrik Tenaga Uap dan Masyarakat di Desa Tubanan Kabupaten Jepara - Tiyani, Vina Yunia; Anitasari, Rahayu Fery (Faculty of Law, Universitas Negeri Semarang, 2024)
Issuers have an obligation to submit financial reports as stipulated in Law No. 8 of 1995 to the Financial Services Authority by applying the principle of openness. Submission of financial statements is accompanied by publishing the financial statements on the website of a public company or issuer which can be used as a material consideration by investors. This research uses a qualitative approach with a juridical-empirical research type. The data sources used are primary and secondary. The results showed that: 1) The Financial Services Authority as the supervisor of the capital market sector has issued regulations that regulate in detail the procedures and obligations that must be fulfilled by issuers, one of which is through examinations related to reporting obligations to realize the principle of openness and provide protection to investors. 2) overstatement can occur intentionally or unintentionally due to misstatements in the financial statements and administrative sanctions are carried out because the violations that occur are administrative in nature. Supervision by the Financial Services Authority but in some cases still has some weaknesses against overstatement carried out by public companies or issuers under the supervision of the Financial Services Authority. Suggestions given by the author are the issuance of regulations related to overstatement, harmonizing regulations and supervision